Otimização do Ensino a Distância: estudo de caso em uma instituição de ensino superior privada - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The demand for education grows around the world at a rate equivalent to the improvement of socioeconomic needs. With this, access to quality education has been influenced by information management, which is necessary to meet market demands. In order to serve the market, there is a strong pressure on educational institutions regarding the insertion of new methods and techniques that may involve the student in a constant learning activity. In this scenario, the Distance Learning Modality (DLM) has attended to its public with the proposal to offer knowledge with speed and convenience. The provision of E-learning courses requires compliance with specific regulations to ensure the quality of the teaching and learning process, as well as the evaluation of students and the institution's own DLM system as a whole. Thus, this research aims to propose a model for improving the pedagogical procedures applied to the DLM in an HEI. The results of this research enabled an analysis of the resources offered by the HEI in the DLM mode, which shows that the services provided can be improved, based on a more adequate follow-up, using more elaborate activities and enabling the process of teaching-learning to become more efficient in favor of the student using the resources for the training itself.
Keywords: Educação a Distância; Processo de Ensino Aprendizagem e Qualidade; Gestão da informação; Ensino à Distância (EaD); ENGENHARIAS: ENGENHARIA DE PRODUÇÃO